Egocentric Navigation Abilities Predict Episodic Memory Performance - Committeri, Giorgia; Fragueiro, Agustina; Campanile, Maria Maddalena; Lagatta, Marco; Burles, Ford; Iaria, Giuseppe; Sestieri, Carlo; Tosoni, Annalisa (Frontiers in Human Neuroscience, 2020)
The medial temporal lobe supports both navigation and declarative memory. On this basis, a theory of phylogenetic continuity has been proposed according to which episodic and semantic memory have evolved from egocentric (e.g. path integration) and allocentric (e.g. map-based) navigation in the physical world. Here, we explored the behavioral significance of this neurophysiological model by investigating the relationship between the performance of healthy individuals on a path integration and an episodic memory task. We investigated the path integration performance through a proprioceptive Triangle Completion Task, and assessed episodic memory through a picture recognition task. We evaluated the specificity of the association between performance in these two tasks by including in the study design a verbal semantic memory task. We also controlled for the effect of attention and working memory, and tested the robustness of the results by including alternative versions of the path integration and semantic memory tasks. We found a significant positive correlation between the performance on the path integration and the episodic memory tasks, but not the semantic memory task. This pattern of correlation was not explained by general cognitive abilities and persisted also when considering a visual path integration task and a non-verbal semantic memory task. Importantly, a cross-validation analysis showed that participants’ egocentric navigation abilities reliably predicted episodic memory performance. Altogether, our findings support the hypothesis of a phylogenetic continuity between egocentric navigation and episodic memory, and pave the way for future research on the causal role of egocentric navigation on multiple forms of episodic memory.